Cisco CCSP SNRS quick reference - Mason, Andrew (Cisco Press, 2009)
Reference for students studying for the Cisco Securing Networks with Routers and Switches exam.
Print version record
Keywords: Computer networks -- Security measures; Routers (Computer networks); Réseaux d'ordinateurs; Sécurité; Mesures; Routeurs (Réseaux d'ordinateurs); Computer networks; Security measures